2014
DOI: 10.2220/biomedres.35.329
|View full text |Cite
|
Sign up to set email alerts
|

A novel type of cells expressing GP2 in the respiratory epithelium of the paranasal sinuses in mice

Abstract: GP2, a GPI-anchored glycoprotein, is a useful marker of M cells in Peyer's patches. Our immunostaining of the paranasal sinuses in mice detected a condensed distribution of GP2-immunoreactive cells within the epithelium, apart from lymphoid tissues. In the paranasal sinuses, the cells exhibited a unique morphology characterized by a slender neck portion and huge terminal bulb, quite different from M cells. Electron microscopically, the GP2 immunoreactivity centered on the luminal plasma membrane of the termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This protein is also a well$known functional marker of intestinal M cells; GP2 appears in the later stage of M-cell differentiation, and its expression has been correlated with the uptake capacity of luminal microbeads (Hase et al 2009a;Kimura et al 2015). In the head region of mice, numerous GP2-expressing non-ciliated cells were found to be distributed in the epithelium covering the paranasal sinuses, tear ducts, and conjunctiva (Kimura et al 2014; our unpublished data).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This protein is also a well$known functional marker of intestinal M cells; GP2 appears in the later stage of M-cell differentiation, and its expression has been correlated with the uptake capacity of luminal microbeads (Hase et al 2009a;Kimura et al 2015). In the head region of mice, numerous GP2-expressing non-ciliated cells were found to be distributed in the epithelium covering the paranasal sinuses, tear ducts, and conjunctiva (Kimura et al 2014; our unpublished data).…”
Section: Discussionmentioning
confidence: 71%
“…Histochemical studies suggested that GP2-expressing cells in the paranasal sinuses and conjunctiva were a lineage of goblet cells because they were more or less positive for Periodic Acid Schiff (PAS) staining (Kimura et al 2014 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the persistently altered genes, Lox and Gp2 , have not been previously implicated in mouse models of active chronic CS exposure. The persistent upregulation of Gp2 , a gene expressed in goblet cells [33] may link it to the heightened mucosal immune response induced by CS exposure [17]. Lox , the only significantly bi-directionally persistently altered gene encodes the precursor protein lysyl oxidase, required to crosslink collagen and elastin, which makes it critical to vascular and extracellular matrix remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Although GP2 is one of the main secretory products of the pancreas, other secretory cells, such as conjunctival goblet cells, have an ability to produce GP2 (12). Epithelial cells dispersed in the respiratory epithelium of the paranasal sinuses were weakly positive for periodic acid-Schiff (PAS) reaction but intensely immunolabeled with the GP2 antibody (11). Furthermore, epithelial cells distributed in the lacrimal canaliculi, lacrimal sac, and nasolacrimal duct contained GP2 along the basolateral membrane and showed a sign of the release of GP2 into the lumen (12).…”
mentioning
confidence: 99%